Mind–body therapies and their interplay with the immune system in children and adolescents: a protocol for a systematic review and meta-analysis - Steven Schepanski; Gonza B Ngoumou; Anna Katharina Koch; Marleen Schröter; Robert Roehle; Georg Seifert (Systematic Reviews)
Abstract Background Chronic inflammation is a critical public health concern that, in children and adolescents, increases the long-term risk of a variety of different health issues. While mind–body therapies like yoga, meditation, and acupuncture have shown promise in modulating immune responses in adults, their safety and effectiveness in pediatric populations remain underexplored. This protocol outlines the methodology for a systematic review and meta-analysis aimed at evaluating the effects of mind–body therapies on immune modulation in children and adolescents. Methods This systematic review and meta-analysis will follow PRISMA 2020 guidelines. We will include randomized controlled trials, non-randomized controlled trials, cohort studies, and case–control studies that examine the relationship between mind–body therapies and immune markers in pediatric populations. Electronic searches will be conducted in MEDLINE, Embase, PsycINFO, CINAHL, Web of Science, and the Cochrane Library, supplemented by trial registries. Risk of bias will be assessed using the Cochrane Risk of Bias Tool (RoB 1), the Risk of Bias in Non-randomized Studies of Interventions (ROBINS-I), and the Newcastle–Ottawa Scale (NOS). Two independent reviewers will screen studies, extract data, and assess study quality, with a third reviewer resolving any discrepancies. Results will be synthesized both narratively and through meta-analysis using R software. Discussion The review will evaluate the effectiveness and safety of mind–body therapies on immune markers in children and adolescents. The synthesized evidence will guide clinical practice and public health policies in integrating mind–body therapies into pediatric care. The findings will also provide a foundation for future research and policymaking in this area. Systematic review registration PROSPERO CRD42024546585.